Relationship of actual nutrition with estimates of the cognitive function of the population of Novosibirsk - A. K. Kuntsevich; S. V. Shishkin; E. G. Verevkin; S. V. Mustafina; O. D. Rymar (Бюллетень сибирской медицины)
Objective. To study in cross-sectional research the association of actual nutrition with estimates of cognitive function (CF) in the population of men and women of middle and older age (45–69 years).Materials and methods. The study was conducted in the framework of the international project HAPIEE on a random subsample (2,159 men, 2,525 women) of residents of Novosibirsk. Evaluation of CF was carried out using standard methods (test for direct reproduction of 10 words, test for speech activity (associative thinking) and test for delayed reproduction). Nutrition data was obtained from population surveys in the HAPIEE project using a questionnaire to assess the frequency of food consumption. Statistical data processing was performed using the SPSS 13.0 application package. The GLM procedure was used, allowing to take into account the influence of related factors. Differences were considered statistically significant at p < 0.05.Results. The presence of a significant correlation between the actual nutrition with standardization by age, body mass index and level of education with CF estimates was found. It has been shown that higher consumption of fruits and vegetables was significantly associated with higher scores in both men and women. Women, unlike men, also showed significantly higher CF estimates for consumption of rice, meat products and dairy products. In addition, there was a negative association of CF with the consumption of a number of products. Men showed a significant decrease in the estimates of CF with the consumption of sugar and fats; in women, in the consumption of white bread, sugar and fat.Conclusion: the results of our study showed the presence of a significant association of CF estimates with the level of consumption of a number of products, both positive and negative, in middle-aged and older people. These data may be useful in the development of nutritional recommendations for the prevention of violations of CF.